Pain in Parkinson's disease - Ha, Ainhi D.; Jankovic, Joseph (Movement Disorders, 2012)
Pain and other nonmotor symptoms in PD are increasingly recognized as a major cause of reduced health-related quality of life. Pain in PD may be categorized into a number of different subtypes, including musculoskeletal, dystonic, radicular neuropathic, and central pain. The onset of pain can vary in relation to motor symptoms, and may precede the appearance of motor symptoms by several years, or occur after the diagnosis of PD has been made. Pain in PD is frequently under-recognized and is often inadequately treated. Levodopa-related dystonia may respond to manipulation of dopaminergic medication. Dopaminergic therapy may also improve musculoskeletal pain related to rigidity and akinesia, as well as akathisia in PD. Botulinum toxin injections can be effective for treatment of painful focal dystonia. Pain and dysesthesia have been reported to improve with DBS, in some cases. Increased understanding of basal ganglia pathways has provided further insights into the pathogenesis of pain in PD, but the exact mechanism of pain processing and modulation remains unclear. © 2011 Movement Disorder Society
Keywords: Parkinson's disease; dystonia; musculoskeletal; nonmotor; pain